2018
DOI: 10.1177/0954407018762587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of throat area and inlet area of intake port on mixture formation of gasoline direct injection engines

Abstract: To study the effects of intake port structure parameters (inlet area and throat area) of a gasoline direct injection engine on mixture formation, a steady-flow test and transient simulation with four kinds of intake ports (named Cases 1–4) were simulated using AVL FIRE; a four-valve, four-cylinder gasoline direct injection engine with Case 1 was also operated under wide-open-throat conditions with a speed of 5500 r/min as the test basis. According to the simulation results, the flow coefficient increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Pogorevc and Kegl 16 proposed a method to improve the intake system to increase the in-cylinder charging efficiency. Zheng et al 17 simulated a steady-flow test and transient simulation with four kinds of intake ports (named Cases 1–4) to study the effects of intake port structure parameters (inlet area and throat area) of a gasoline direct injection engine on mixture formation. The results showed that the flow coefficient increased as the throat increased and the inlet areas decreased, and conversely changing them could improve the tumble ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Pogorevc and Kegl 16 proposed a method to improve the intake system to increase the in-cylinder charging efficiency. Zheng et al 17 simulated a steady-flow test and transient simulation with four kinds of intake ports (named Cases 1–4) to study the effects of intake port structure parameters (inlet area and throat area) of a gasoline direct injection engine on mixture formation. The results showed that the flow coefficient increased as the throat increased and the inlet areas decreased, and conversely changing them could improve the tumble ratio.…”
Section: Introductionmentioning
confidence: 99%
“…10 The mass of entrained air was also found to increase with fuel injection pressure. 11 In-cylinder turbulence was increased with the introduction of high-pressure direct-injection 12 but the effect on tumble was found to be very less. 13 High pressures also permit late injection into the compression stroke without compromise on particulate emission.…”
Section: Introductionmentioning
confidence: 99%
“…For the parameter optimization stage, to get the better performance of intake ports, a lot of work has been done on the relationship between the defined parameters and the intake flow characteristics. 14,15 Generally, the parameters of intake ports are usually adjusted by the experience from the experimental database or the numerical simulation results, [16][17][18] but it is hard to get the optimum results due to the cost of time and money. Thus, the genetic algorithm (GA) has been applied to the optimization of the intake port parameters in recent years.…”
Section: Introductionmentioning
confidence: 99%